Stress versus immunity - Liaudat, Ana Cecilia (2018)
The aim of this mini-review is to discuss the effects of early life stress on some aspects of the immune response. Results from research models applied to study this subject, showed that stimuli that cause stress during early life alters the development of offspring´s immune system, making it more prone to suffer different diseases.